COMPARISON OF BLOOD LOSS IN PATIENTS UNDERGOING ABDOMINAL MYOMECTOMY TREATED WITH AND WITHOUTSINGLE PREOPERATIVE DOSE OF PER VAGINAL MISOPROSTOL (The Research of Medical Science Review, 2025)
Objective: To compare intraoperative blood loss in patients undergoing abdominal myomectomy with and without a single preoperative dose of per vaginal misoprostol. Methods: This randomized controlled trial was conducted at the Department of Gynecology and Obstetrics, Unit 1, Sir Ganga Ram Hospital, Lahore. Sixty patients aged 20–45 years with a single intramural fibroid (10–20 cm) were randomized into two groups: Group A received 400 µg of misoprostol per vaginally 30 minutes before surgery, and Group B received no preoperative misoprostol. Intraoperative blood loss was measured using the weight difference of surgical sponges and the volume in suction bottles. Results: The mean intraoperative blood loss was significantly lower in Group A (310.2 ± 30.5 mL) than in Group B (415.6 ± 85.4 mL, p < 0.001). The mean hemoglobin drop was also smaller in Group A (1.1 ± 0.3 g/dL) compared to Group B (1.7 ± 0.4 g/dL, p < 0.001). Blood transfusion was required in 6.7% of patients in Group A versus 26.7% in Group B (p = 0.03). Mild side effects such as nausea and abdominal pain were observed in the misoprostol group. Conclusion: It is concluded that a single preoperative dose of per vaginal misoprostol significantly reduces intraoperative blood loss, hemoglobin drop, and the need for blood transfusions during abdominal myomectomy. While mild side effects were reported, they were manageable, making misoprostol a safe and effective intervention for reducing surgical morbidity. Further studies are recommended to validate these findings.